Effects of laser polishing on surface quality and mechanical properties of PLA parts built by fused deposition modeling. Issue 3 (2nd August 2019) - Chen, Lan; Zhang, Xinzhou; Gan, Shuyuan
ABSTRACT: Fused deposition modeling (FDM) produces parts through layer by layer on the top of each other, making it almost impossible to obtain smooth printed parts. Hence, there is a huge demand for the postprocessing of the FDM‐printed parts. Laser polishing is a novel technique that can be used to polish products to obtain a smoother surface. The aim of this work was to explore the feasibility of surface‐finishing FDM‐printed polylactic acid (PLA) parts by laser polishing. The surface roughness, surface morphology, dynamic mechanical analysis (DMA), and tensile properties were investigated. The results indicated that the lower laser power and the bigger laser beam diameter within a certain range could facilitate the formation of smoother surface. With optimized parameters, the surface roughness was reduced by 90.4%. DMA showed that the storage modulus ( E' ) and glass transition temperature of PLA specimens were significantly improved due to the decrease of molecular mobility of denser structures. Moreover, the tensile strength and Young's modulus of the PLA specimen were also significantly increased after laser polishing. The fracture morphologies were observed, and the possible strengthening mechanism was also discussed. These results indicated that laser polishing could be an efficient method for surface polishing of FDM parts. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2020, 137, 48288. Abstract :